Globalization and technological capabilities: evidence from Mexico’s patent records ca. 1870-1911 - Beatty, Edward (Estudios de Economía, 2016)
Using a new database of all patents issues in Mexico between 1870 and 1911, this paper explores the impact of the vast wave of technology imports into Mexico during the nineteenth century period of globalization. Historians have established that massive technology imports made possible sustained economic growth and early industrialization during this period, but have not systematically explored the degree to which the skills and know-how embodied in new imported technologies stimulated adaptive and inventive activity in Mexico. Did imported technologies stimulate local technological creativity, or were Mexican technicians largely isolated from the adoption and use of imported techniques? The evidence shows that imports did stimulate patenting activity by Mexicans, although this response was modest in relation to increased patenting by inventors from North Atlantic countries. In general, Mexican inventors focused on activities outside the core technical advances on the global frontier, and often on activities that were more entrepreneurial than technical, although we can observe several important exceptions. These findings support the argument that technological capabilities were scarce in Mexico and local technicians had few opportunities to engage with and learn from imported know-how.